MEMBANGUN KEMITRAAN BANK SYARIAH DENGAN PENDEKATAN SHARIAH MARKETING - Arief Yulianto (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
Amidst the competitions among shariah bank demanding the shariah bank to have marketing strategies in order to keep a sustainable relation between bank and customers. It was revealed from this research that some variables: product attributes, the quality of service to the Islamic approach to marketing, reputation, satisfaction, affective commitment, continuous commitment and customer loyalty can be accepted as the decisive variables in deciding the good marketing relationship between shariah bank and customers.